“All Politics is Local”: A Sociocognitive Investigation of Contexts as Indigenous Peculiarities in Gubernatorial Inaugurals - Adebayo Rasheed Mabayoje (Universitas Sanata Dharma, 2022)
Devised by Tip O'Neill,